Prevalence and associations of anisometropia and aniso-astigmatism in a population based sample of 6 year old children. Issue 5 (18th April 2006) - Huynh, S C; Wang, X Y; Ip, J; Robaei, D; Kifley, A; Rose, K A; Mitchell, P
Abstract : Aim: To study the distribution of anisometropia and aniso-astigmatism in young Australian children, together with clinical and ocular biometry relations. Method: The Sydney Myopia Study examined 1765 predominantly 6 year old children from 34 randomly selected Sydney schools during 2003–4. Keratometry, cycloplegic autorefraction, and questionnaire data were collected. Results: Spherical equivalent (SE) anisometropia (⩾1 dioptre) prevalence was 1.6% (95% confidence interval (CI) 1.1% to 2.4%). Aniso-astigmatism (⩾1D) prevalence was 1.0% (CI: 0.6% to 1.6%). Both conditions were significantly more prevalent among moderately hyperopic (SE ⩾2.0D) than mildly hyperopic (SE 0.5–1.9D) children. Myopic children (SE ⩽−0.5D) had higher anisometropia prevalence. Neither condition varied by age, sex, or ethnicity. In multivariate analyses, anisometropia was significantly associated with amblyopia, odds ratio (OR) 29, (CI: 8.7 to 99), exotropia (OR 7.7, CI: 1.2 to 50), and neonatal intensive care unit (NICU) admission (OR 3.6, CI: 1.1 to 12.6). Aniso-astigmatism was significantly associated with amblyopia (OR 8.2, CI: 1.4 to 47), maternal age >35 years (OR 4.0, CI: 1.3 to 11.9), and NICU admission (OR 4.6, CI: 1.2 to 17.2). Anisometropia resulted from relatively large interocular differences in axial length (p<0.0001) and anterior chamber depth (p = 0.0009). Aniso-astigmatism resulted from differences in corneal astigmatism (p<0.0001). Conclusion: In this predominantly 6 year old population, anisometropia and aniso-astigmatism were uncommon, had important birth and biometry associations, and were strongly related to amblyopia and strabismus.